Relationship between time limit at maximal aerobic velocity and swimming performance in young swimmers - Almeida, T.; Macedo, A. G.; Massini, D. A.; de Castro, E. A.; Espada, M. C.; Filho, D. M. P. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
Maximal aerobic velocity (MAV) is usually used by coaches for intensity zones prescription as it combines effort economy with V.O2max. This study aims to characterize and compare swimmers' physiological responses in a time-limit (tLim) at MAV test and determine whether these variables could relate to performance. 13 well-trained male swimmers performed an incremental test composed of 6 sets of 250 meters plus 200 meters at maximum intensity in front-crawl to obtain V.O2max and MAV. 48 hours later, a continuous test at MAV (tLim-MAV) to exhaustion was used for tLim, maximum V.O2 of the test (V.O2peak), percentage time close to V.O2max (>=90%V.O2max), and V.O2 kinetics (V.O2k) assessment. A gas analyzer attached to a swimming snorkel, was used to analyze the expired gases, and an underwater light pacer to velocity control. Swimmers' records at 400 (T400) and 800 m (T800) freestyle were recorded. The V.O2peak of the tLim-MAV test (57.0±4.8 ml kg1 min-1) was not different from the V.O2max (57.1±5.7 ml kg-1 min-1). The tLim (243.6±59.3 s) showed correlations with T800 (r = 0.70, p < 0.01) and >=90%V. O2max (44.4±18.9 %) (r = 0.83, p < 0.01) and an inverse correlation with MAV (1.30±0.07 m s-1) (r = -0.72, p < 0.01). The V.O2k parameters did not influence the other variables of the tLim-MAV test. MAV, V.O2max, and V.O2peak of the tLim-MAV were related with the T400 performance (r = -0.54, p < 0.05; r = -0.77, p < 0.01 and r = -0.73, p < 0.05, respectively). The inverse relationship between tLim and MAV suggests that the ability to tolerate this relative intensity in time, by itself, is not related to swimming performance, which was confirmed by the direct relationship with T800 since swimmers with higher tLim present worse performances. This data may be important in prescribing training sets for MAV since faster swimmers should perform sets with shorter repetitions to avoid fatigue early in the task. Thus, we suggest applying tLim-MAV tests to swimmers to better individualize the training prescription. The MAV, V.O2max, and V.O2peak, being the variables that are most related to performance, should be considered, and the development of these variables should assume a predominant role in training protocols.